City profile: Is Pyongyang a post-socialist city?. (January 2021) - Em, Pavel P.; Ward, Peter
Abstract: Pyongyang is often used as a metonym for North Korea's leaders and the issues their policies create for the world. However, the profound internal changes rapidly transforming the city since the 1990s make Pyongyang a fascinating urban case study. This profile is an attempt to shed light on one of the most 'mysterious' cities in the world; firstly, through analysis of its socio-economic dynamics and, secondly, by examining its possible transformation into a post-socialist city through a comparison of its spatial characteristics with Central and East European capitals. We also consider how the city retains substantial state socialist characteristics. Highlights: The paper updates the city profile of Pyongyang and examines whether it is a post-socialist city after the onset of marketization. Pyongyang's urban development trajectory after the onset of marketization is examined and compared with Central and East European capitals after the collapse of the Socialist Bloc. We also seek to answer the question of whether Pyongyang is a post-socialist city through an analysis of its urban spatial characteristics.